Novel MRSA-targeting phage MetB16: Genomic features, structural insights, and therapeutic applications - Erdogdu, Berna; Dokuz, Senanur; Gungor, Gorkem; Lin, Wei; Tong, Yigang; Ozbek, Tulin (Tubitak Scientific & Technological Research Council Turkey, 2025)
Background/aim: Recent reports have indicated that multidrug-resistant strains of S. aureus, including methicillin-resistant strains, may pose a significant threat to public health and global economic stability. Materials and methods: In this study, we present the isolation and comprehensive characterization of a novel phage, derived from clinically isolated MRSA strains. Results: MetB16 exhibited an incubation period of approximately 20 min, a lysis period of around 45 min, and a burst size of 127 Plaque Forming Units (PFU)/cell. The phage demonstrated remarkable biological stability across a pH spectrum of 4.0-9.0 and maintained integrity within a temperature range of 37 and-80 degrees C. Scanning transmission electron microscopy and phylogenetic analyzes classified MetB16 as belonging to the Triavirus genus, representing a novel species within the Triaviruses. Whole-genome sequencing revealed a 45,295 bp-long genome size with a G + C content of 33.34%. Notably, bioinformatic analyses identified random integration sites within the MRSA genome. Functional annotation of the genome uncovered 72 open reading frames (ORFs), of which 34 encoded hypothetical proteins of unknown function, and these ORFs were associated with phage structure, packaging, host lysis, DNA metabolism, and additional functions. To elucidate the therapeutic potential of temperate phages, detailed structural analyses were conducted on key proteins, including holin, endolysin, and minor tail proteins of MetB16. Conclusion: This study provides for the first time, the preliminary studies on the biological properties of MetB16 and comprehensive data facilitating an in-depth analysis of the mechanism underlying phage-host interactions, serving as a valuable reference for the evaluation of temperate phages in phage therapy.
Keywords: Methicillin-resistant Staphylococcus aureus (MRSA); prophage induction; modeling phage protein; phage bioinformatics; BACTERIOPHAGES; INFECTIONS; DIVERSITY; Life Sciences & Biomedicine - Other Topics